Ion induced high energy electron emission from copper - Ruano Sandoval, Gustavo Daniel (2008)
We present measurements of secondary electron emission from Cu induced by low energy bombardment (1–5 keV) of noble gas (He+, Ne+ and Ar+) and Li+ ions. We identify different potential and kinetic mechanisms and find the presence of high energetic secondary electrons for a couple of ion-target combinations. In order to understand the presence of these fast electrons we need to consider the Fermi shuttle mechanism and the different ion neutralization efficiencies.